Knowledge map in biomaterials and related immune response: a scientometric analysis - Yu, Chongqing; Xu, Chi; Wang, Tao; Xu, Jie (Frontiers in Materials, 2025)
BackgroundBiomaterials have seen extensive use in biomedicine in the past decade. However, being foreign substances when implanted in the human body, they inevitably trigger immune responses. This study aimed to summarize existing articles on biomaterials and immune responses and explore their latest trends.MethodsWe used the Web of Science Core Collection database (WoSCC) to access literature related to biomaterials and immune response. This comprehensive review of the knowledge domain allowed us to identify potential future research directions.ResultsIn this study, we analyzed 5,993 articles on biomaterials and immune response published between 1990 and 2022. Badylak, SF, stood out with the highest number of publications, the highest h-index, and the most average citations. The Journal of Biomaterials secured the top position as the most productive journal with the highest citation count. The emerging research hotspots are centered in regeneration medicine around keywords such as “biocompatibility,” “wound healing,” “osteogenesis,” “angiogenesis,” and “bone regeneration.”ConclusionThe present study summarizes the global trends in biomaterials and immune response. Future efforts should concentrate on advancing the application of biomaterials in the medical field, conducting in-depth mechanistic studies, exploring the intricacies of immune responses, and ensuring the biosafety of biomaterials.